ЦИФРОВІЗАЦІЯ ПРОЦЕСІВ ДЕРЖАВНОГО РЕГУЛЮВАННЯ ГРАНТОВОЇ ПІДТРИМКИ МАЛОГО ТА СЕРЕДНЬОГО БІЗНЕСУ: ВИКЛИКИ ТА ПЕРСПЕКТИВИ ДЛЯ УКРАЇНИ - Ярослав Савишен (Публічне управління і право: історія, теорія, практика, 2026)
The article is devoted to the digitalization of public regulation of grant support for small and medium-sized enterprises in Ukraine under the conditions of full-scale war and the accelerated transformation of public administration. The relevance of the topic is determined by the contradiction between the technological capabilities of the state’s digital infrastructure and the insufficient institutional capacity of public authorities to integrate these tools into the logic of managerial decision-making. Based on the analysis of Ukrainian and foreign scholarly sources, as well as OECD and European Union materials, the article outlines the foundations of digital transformation in public administration and distinguishes between digitalization, digital transformation, and digital governance as levels of institutional maturity. The financing of digitalization in Ukraine’s public sector during 2019–2024 is analyzed, and the growing role of international donor assistance after the beginning of the full-scale invasion is emphasized. A comparative analysis of traditional and digital models of state business support shows that the transition to a digital format does not by itself eliminate structural weaknesses of public administration without a change in decision-making logic. Drawing on the experience of European Union grant programs (COSME, Horizon Europe, SME Fund) and OECD conclusions, the key challenges of digitalizing grant administration are systematized: institutional fragmentation, cyber risks, regional inequality in digital access, and the desynchronization of digitalization rates between the public sector and the business environment. A conceptual model of digital administration of SME grant support is proposed, based on a single digital entry point with standardized application evaluation criteria, hybrid access channels, and gradual integration with international donor platforms while preserving the institutional autonomy of the national public administration system. The scientific novelty lies in substantiating a systemic approach in which public administration acts as an active coordinator of a holistic institutional architecture of grant support. The practical significance of the study lies in the possibility of applying the proposed model to improve state support for small and medium-sized enterprises in Ukraine.